Stereotactic arrhythmia radioablation (STAR) opens a new era in the treatment of arrhythmias? - Zhang, Shuang; Hu, Lin; Tang, Hanze; Liao, Liyi; Li, Xuping (Frontiers in Cardiovascular Medicine, 2024)
Tachyarrhythmias are common cardiovascular emergencies encountered in clinical practice. Among these, atrial fibrillation (AF) and ventricular tachycardia (VT) pose significant hazards due to their prevalence and severity. Initially, non-invasive pharmacological antiarrhythmic interventions were the primary treatment modality; however, due to their limited control rates and side effects, invasive therapies have been introduced in recent years. These include catheter ablation, alcohol ablation, cardiac implantable electronic devices, and heart transplantation. Nonetheless, for some patients, invasive treatments do not offer a definitive cure for arrhythmias and carry the risk of recurrence, especially with AF and VT, where the relapse rates are high and the treatment for VT is correlated with the type of tachycardia present.Currently, novel non-invasive treatment methods are emerging, with stereotactic radioablation therapy becoming an effective alternative for the management of refractory tachyarrhythmias. This review provides an overview of the application background of Stereotactic Arrhythmia Radioablation (STAR) therapy and promising results from its use in animal models and clinical applications.Cardiovascular diseases are the leading cause of death globally. It is estimated that about 17.9 million people die from cardiovascular diseases each year, accounting for 31% of all global deaths